Future Dietitian 2025: informing the development of a workforce strategy for dietetics. Issue 1 (21st September 2017) - Hickson, M.; Child, J.; Collinson, A.
Abstract: Background: Healthcare is changing and the professions that deliver it need to adapt and change too. The aim of this research was to inform the development of a workforce strategy for Dietetics for 2020–2030. This included an understanding of the drivers for change, the views of stakeholders and recommendations to prepare the profession for the future. Methods: The research included three phases: (i) establishing the context which included a literature and document review (environmental scan); (ii) discovering the profession and professional issues using crowd‐sourcing technology; and (iii) articulating the vision for the future using appreciative inquiry. Results: The environmental scan described the current status of the dietetic profession, the changing healthcare environment, the context in which dietitians work and what future opportunities exist for the profession. The online conversation facilitated by crowd‐sourcing technology asked the question: 'How can dietitians strengthen their future role, influence and impact?' Dietitians and interested stakeholders (726 and 109, respectively) made 6130 contributions. Seven priorities were identified and fed into the appreciative inquiry event. The event bought together 54 dietitians and analysis of the discussions generated five themes: (i) professional identity; (ii) strong foundations‐creating structure and direction for the profession; (iii) amplifying visibility and influence; (iv) embracing advances in science and technology; and (v) career advancement and emerging opportunities. Conclusions: A series of recommendations were made for the next steps in moving the workforce to a new future. The future for dietetics looks bright, embracing technology, as well as exploring different ways of working and new opportunities, as this dynamic profession continues to evolve.